Disclosure Of Enterprise Risk Management (ERM), Company Value, And Profitability As Moderating Factors - Endang Dwi Wahyuni; Indah Oktavia (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This research aims to empirically prove the effect of enterprise risk management disclosure on company value with profitability as a moderating factor. The object of this research is the utility, transportation, and infrastructure sector companies in the 2016-2017 period. The sampling of this research is 20 companies using the purposive sampling technique. The research data obtained were then analyzed using simple regression analysis; and to determine the effect of moderating factors on the relationship between independent and dependent variables, the data were analyzed using Moderating Regression Analysis (MRA). The results of this research prove that Enterprise Risk Management influences company value. The subsequent testing proved that profitability can moderate the relationship between Enterprise Risk Management and company value as evidenced by an increase in the adjusted R-square value